Herpez Zoster in Teens - Flora Ramona Sigit Prakoeswa; Hindun Luthfia Rosyida; Rika Ariyanti (Asian Journal of Social and Humanities, 2023)
Herpes Zoster (HZ) is a reactivation of the Varicella Zoster Virus (VVZ), which is characterized by an acute unilateral vesicular eruption grouped with radicular pain around the dermatome. The incidence of HZ increases with age and is rare in children. The prevalence of HZ in children can occur, if they have a history of primary intrauterine infection, are immunocompromised, and who are infected with varicella in the first year of life. One daughter, Ms. B, 15 years old, came to the Skin and Venereology Clinic, PKU Muhammadiyah Surakarta Hospital on December 28, 2022 with complaints of itching and heat, a lesion in the form of multiple clustered vesicles, round in shape, with a size of 0.3-0.5 cm above the skin, erythematous, unilateral, not crossing the midline, the age of the vesicles in one group is the same, but with other groups it is not the same, the skin between groups is normal. Treatment was given acyclovir 4x800 mg per day taken orally for 5 days, triamcinolone 4 mg/day, compressed NaCl 15 minutes 2x daily, caaladine lotion 2x daily on intact lesions and mupirocin calcium on open wounds